Putative novel mediators of acute kidney injury in critically ill patients: handling by continuous venovenous hemofiltration and effect of anticoagulation modalities. Issue 1 (December 2015) - Schilder, Louise; Nurmohamed, S.; Wee, Pieter; Paauw, Nanne; Girbes, Armand; Beishuizen, Albertus; Beelen, Robert; Groeneveld, AB
Abstract Background Novel putative mediators of acute kidney injury (AKI) include immune-cell derived tumour necrosis factor-like weak inducer of apoptosis (TWEAK), angiopoietin-2 (Ang-2) and protein pentraxin-3 (PTX3). The effect of continuous venovenous hemofiltration (CVVH) and different anticoagulation regimens on plasma levels were studied. Methods At 0, 10, 60, 180 and 720 min of CVVH, samples were collected from pre- and postfilter blood and ultrafiltrate. No anticoagulation (n  = 13), unfractionated heparin (n  = 8) or trisodium citrate (n  = 21) were compared. Results Concentrations of TWEAK, Ang-2 and PTX3 were hardly affected by CVVH since the mediators were not (TWEAK, PTX3) or hardly (Ang-2) detectable in ultrafiltrate, indicating negligible clearance by the filter in spite of molecular sizes (TWEAK, PTX3) at or below the cutoff of the membrane. Heparin use, however, was associated with an increase in in- and outlet plasma TWEAK. Conclusion Novel AKI mediators are not cleared nor produced by CVVH. However, heparin anticoagulation increased TWEAK levels in patient's plasma whereas citrate did not, favouring the latter as anticoagulant in CVVH for AKI.